2021
DOI: 10.5688/ajpe7971
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adaptive Learning Technology to Promote Self-Directed Learning in a Pharmacists’ Patient Care Process Course

Abstract: Objective. One goal of pharmacy educators is to help students become self-directed learners. A method that may help achieve this goal is adaptive learning technology (ALT), which provides real-time feedback on students' strengths and weaknesses. The primary objective of this study was to evaluate student changes in self-directed learning (SDL) in a Pharmacists' Patient Care Process (PPCP) course using ALT. Methods. PPCP was delivered using traditional teaching methods in fall 2018 and ALT in spring 2019. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“… 4 In the face of a vast array of learning resources and a learning environment that lacks explicit direction, self-directed learning (SDL) is a skill that they need to acquire in continuing education. 5 However, studies have reported that medical professionals encounter many difficulties during the process of SDL. 6 Similarly, a commentary article mentioned hospital pharmacists may encounter challenges when engaging in SDL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In the face of a vast array of learning resources and a learning environment that lacks explicit direction, self-directed learning (SDL) is a skill that they need to acquire in continuing education. 5 However, studies have reported that medical professionals encounter many difficulties during the process of SDL. 6 Similarly, a commentary article mentioned hospital pharmacists may encounter challenges when engaging in SDL.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, learning is self-directed in the absence of explicit direction 4. In the face of a vast array of learning resources and a learning environment that lacks explicit direction, self-directed learning (SDL) is a skill that they need to acquire in continuing education 5. However, studies have reported that medical professionals encounter many difficulties during the process of SDL 6.…”
Section: Introductionmentioning
confidence: 99%
“…These skills are important because pharmacists are responsible for synthesizing reliable and valid healthcare research and providing it to the patients and communities they serve. This is all the more important during a pandemic, when there is rapidly evolving and sometimes contrasting information available [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the literature have shown that self-directed learning modules (SDLMs) are strong factors in influencing students' learning outcomes in traditional learning settings or distance learning environments [6]. SDLMs have been implemented to undergraduate medical students in biochemistry [7], medical student knowledge and attitudes regarding decision-making capacity [8], teaching kinematics [9], and pharmacists' patient care process course [10], etc.…”
Section: Introductionmentioning
confidence: 99%